International Franchise or Local Brand Management? A Comparative Analysis of Strategic Partnership Models for Three- and Four-Star Hotels in Indonesia - Wala Erpurini; dino gustaf leonandri; nuralamsyah (LP2M IAIN Palopo, 2026)
Purpose: This study aims to comparatively analyze the strategic partnership models of international franchising and local brand management contracts in three- and four-star hotels in Indonesia. The research seeks to examine which model provides greater strategic, financial, and operational advantages from the perspective of hotel owners. The study is guided by the assumption that different branding partnerships generate distinct implications for performance, cost structure, market positioning, and long-term sustainability. Methods: This research employs a qualitative comparative design. Data were collected through in-depth semi-structured interviews with hotel owners and executive managers of three- and four-star hotels operating under international franchise agreements and local brand management contracts in major Indonesian cities. The sampling technique used purposive sampling to ensure participants had direct decision-making authority regarding partnership selection. Data were analyzed using thematic analysis, involving coding, categorization, and cross-case comparison to identify patterns in strategic considerations, financial performance perceptions, brand leverage, operational autonomy, and contractual risk.Results: The findings reveal that international franchise models tend to provide stronger brand recognition, standardized operational systems, and broader access to global distribution networks, but involve higher fees and reduced managerial flexibility. Conversely, local brand management contracts offer greater operational autonomy, lower financial obligations, and better adaptation to domestic market characteristics, although brand equity and international market penetration are comparatively limited. The choice of partnership model is strongly influenced by ownership objectives, capital structure, target market segmentation, and long-term growth strategy.Implications: The study provides practical insights for hotel owners, investors, and policymakers in evaluating strategic partnership options within Indonesia’s mid-scale hospitality sector. The findings suggest that partnership decisions should align with the hotel’s strategic orientation, financial capacity, and competitive positioning. Future research is recommended to incorporate quantitative performance indicators and longitudinal analysis to measure the long-term financial and operational impact of each partnership model.